CMOS imagine sensor based physical unclonable function - Peh, Jia Ming (Nanyang Technological University, 2021)
A certain level of trust and resiliency is anticipated from an image sensor. This report introduces a new inexpensive CMOS image sensor based physical unclonable function (PUF) that may be used in a wide range of privacy, security, and trusted protocols that use the image sensor as a trusted entity. This PUF takes advantage of intrinsic imperfections in the image sensor manufacturing process to produce a unique digital signature. It has a high reliability of 0.99% ranging from -45 to 95°C and voltage variation ranging from 1.6V to 2.0V.